IMPLEMENTASI PASAL 14 AYAT 3 PERATURAN GUBERNUR BALI NOMOR 1 TAHUN 2020 TENTANG TATA KELOLA MINUMAN FERMENTASI DAN/ATAU DETILASI KHAS BALI TERKAIT PEREDARAN ARAK BALI TANPA LABEL DI KABUPATEN BULELENG - Gede Nova Wwahyudi; Si Ngurah Ardhya; Muhamad Jodi Setianto (Universitas Pendidikan Ganesha, 2023)
The purpose of this research is to find out and analyze related to 1) the implementation of Article 14 Paragraph 3 of the Bali Governor's Regulation Number 1 of 2020 concerning the Management of Balinese Fermented and/or Distilled Drinks related to the Distribution of Balinese Arak Without Labels in Buleleng Regency and 2) find out what the consequences are. law against business actors who do not include labels on their product packaging. The type of research used is empirical legal research with descriptive research characteristics. The location of this research was carried out in Buleleng Regency. The data collection techniques used were document study, observation and interviews. The sampling technique used was the Non Probability Sampling technique and the subject determination used the Purposive Sampling technique. Qualitative data processing and analysis techniques. The research results show that 1) The provisions of Article 14 Paragraph 3 of Bali Gubernatorial Regulation No. 1 of 2020 have not been implemented properly. This is reflected in the fact that there are still business actors who do not include labels in accordance with the applicable provisions on their product packaging. The ineffectiveness of these regulations lies in the less than optimal role of the government in terms of outreach to the community and the lack of public legal awareness regarding the existence of Bali Gubernatorial Regulation No. 1 of 2020. 2) Furthermore, the legal consequences for violations of labeling on product packaging can be in the form of administrative sanctions as regulated in Article 61 Republic of Indonesia Government Regulation Number 69 of 1999 concerning Food Labels and Advertisements as well as Article 62 and Article 63 of the UUPK. The administrative sanctions can take the form of confiscation of certain goods, announcement of a judge's decision, payment of compensation, order to stop certain activities that cause consumer losses, obligation to withdraw goods from circulation and revocation of business permits.